(untitled) (Journal of Geography and Environmental Management, 2016)
In the article discusses the organization of natural parks , monuments and sites in the Aktobe region. One of the most effective and efficient forms of conservation of biological diversity is considered scientifically based network of protected areas , which will not only save some unique landscapes and ecosystems, species and communities , but also the natural environment as a whole.